2019
DOI: 10.1002/jib.565
|View full text |Cite
|
Sign up to set email alerts
|

The temperature dependent functionality ofBrettanomyces bruxellensisstrains in wort fermentations

Abstract: In recent years, Brettanomyces bruxellensis has found increasing application in brewery fermentations. Indeed, B. bruxellensis contributes to the flavour profile of many Belgian beers, typically during secondary or spontaneous fermentation. In North America, the yeast is used in primary fermentation to produce beers with ‘Brett’ characteristics with ‘fruity’ and/or ‘funky’ sensory profiles associated with the production of volatile esters and phenols. However, little is understood about the factors that influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…A study by Michel et al (2017) using RSM to optimize fermentation conditions of a Torulaspora delbrueckii strain in wort showed that high sensorial desirability of the produced beer was achieved at a high pitching rate of 60 × 10 6 cells/mL. Furthermore, the fermentation temperature can have significant influences on the production of fermentation by-products across yeast genera, e.g., a higher temperature resulting in increased ester production (Verstrepen et al, 2003;Michel et al, 2017;Tyrawa et al, 2019).…”
Section: Response Surface Methodologymentioning
confidence: 99%
“…A study by Michel et al (2017) using RSM to optimize fermentation conditions of a Torulaspora delbrueckii strain in wort showed that high sensorial desirability of the produced beer was achieved at a high pitching rate of 60 × 10 6 cells/mL. Furthermore, the fermentation temperature can have significant influences on the production of fermentation by-products across yeast genera, e.g., a higher temperature resulting in increased ester production (Verstrepen et al, 2003;Michel et al, 2017;Tyrawa et al, 2019).…”
Section: Response Surface Methodologymentioning
confidence: 99%
“…Interestingly, B. bruxellensis has the ability to ferment some complex carbohydrates such as maltodextrins (i.e., maltopentaose and maltotetraose), which causes a high attenuation and may have a role in the dry mouthfeel of beers where B. bruxellensis is used [168]. The use of sugar for this yeast varies considerably [99,103,104,171]; however, the alcohol content of the beer obtained, even in maltose-negative yeasts, seems to be too high for NABLAB production [113,172]. In addition, another point to be considered is the careful selection of the strain to be used, as some strains of B. bruxellensis have the potential to produce biogenic amines, biologically dangerous substances [173].…”
Section: Brettanomyces Bruxellensismentioning
confidence: 99%
“…contributed to obtaining the product with the strongest antioxidant properties, although the activity also decreased with the fermentation time [77]. On the other hand, the fermentation temperature essentially influences the metabolic activity of microorganisms, resulting in products with different sensory characteristics as well as production of bioactive compounds [78]. Neffe-Skoci ńska et al (2017) found that optimal temperature of Kombucha fermentation was 25 • C. The content of glucuronic acid in product obtained at 25 • C was higher than at 20 • C or 30 • C [79].…”
Section: Fermentationmentioning
confidence: 99%
“…as well as AAB and Zygosaccharomyces sp. What is more, the synthesis of vitamin C was better during green tea fermentation, thus Kombucha based on green tea can be characterized by stronger antioxidant activity compared to the infusion of the green tea [78].…”
Section: Vitaminsmentioning
confidence: 99%